Nutritional behavior of Polish canoeist's athletes: The interest of nutritional education - Nowacka, E.; Leszczynska, T.; Kopec, A.; Hojka, D. (Science & Sports, 2016)
Objective: Properly balanced daily diet is necessary to generate energy during exercise and increases the energy substrates de novo synthesis after exercises. The objective of this study was to evaluate the intake of energy, basic nutrients and supplements with daily diets by professional slalom canoeists, which have not been under control of dieticians, before and after the nutritional education. Materials and methods: The intake of nutrients was assessed with 24-h recalls in two seasons during the year for the next two years. After the first year of this study sportsmen and their coaches had individual and group consultations concerning the nutritional guidelines and their nutritional mistakes. Results: Nutritional mistakes of sportsmen relied on incomplete coverage of the recommendations for energy (in the first year of study women met recommendation in 55.3%, men in 62.5% in the second year respectively in 58.6 and 74.4%) and carbohydrates (in the first year of study women met recommendations in 51.7% diet, men in 64.8% in the second year respectively in 59.8 and 81.0%). What is more, almost half of population did not meet recommendations for total fat intake compared to the value of 30% energy from fat. In the first year of study only 50.6% of women and 57.1% of men met these recommendations and in the second year 54.4% women as well as 64.7% men. It was also found that nutritional education might result in improved eating habits. Conclusions: Improvement of nutritional habits after workshops with nutritionists justifies the need to continue nutritional education among professional slalom canoeist and their coaches.